Genome wide association study of antioxidant activity in pigeonpea germplasm - Megha; Nisha Singh; Manju Sharma; Sapna Langyan; Nagendra Kumar Singh (Discover Food, 2024)
Abstract Pigeonpea (Cajanus cajan L.) is a nutritious crop with antioxidant potential, making it valuable for health supplements and medicinal products. Pigeonpea seed coat possess a rich source of antioxidant properties, particularly in dark colour seed coat varieties. Recently, antioxidant-based drugs for the prevention and treatment of complex diseases have evoked a great deal of research interest in natural antioxidants. We resolved genomic regions by conducted a genome-wide association study (GWAS) using a high-throughput 62 K SNP “CcSNPnks” genic chip to identify SNP markers associated with antioxidant properties in 287 diverse panel of pigeonpea genotypes. Evaluated their antioxidant activity using a spectrophotometric technique based on ferric ion-reducing antioxidant potential (FRAP) and calculated the gallic acid equivalents (GAE) per 100 g of extract. Significant differences in antioxidant activities were found among genotypes, ranging from 3.27 mg in ICPL-13271 to 16.85 mg in UP 9-I for ferric iron-reducing activity. The GWAS identified four distinct marker trait association (MTA) that exhibit a strong correlation with antioxidant properties. We identified significant marker trait associations with chr 2 (AX-165372487), chr 6 (AX-165348296) code for RGA1 protein, chr 10 (AX-165367685) codes for alkaline ceramidase (transcript variant), and chr 11 (AX-165411944) codes for (DL)-glycerol-3-phosphatase 2. The identified protein, RGA1, is involved in reducing ROS accumulation in response to stress by up-regulating the transcription of superoxide dismutases. It suppresses GA-induced vegetative growth and floral initiation. Rapidly degraded in response to GA and involved in fruit and flower development. Furthermore, the population structure analysis identified four distinct sub-populations with admixture types, effectively grouping all genotypes based on their ancestry. Our findings advance the understanding of the genetic underpinning antioxidant concentrations, holding potential for applications in crop breeding and aligning with consumer preferences. This study provides a cornerstone for future research into exploiting marker-assisted breeding to produce pigeonpea cultivars.